Rheumatic Musculoskeletal Diseases and COVID-19 A Review of the First 6 Months of the Pandemic - Stradner, Martin H.; Dejaco, Christian; Zwerina, Jochen; Fritsch-Stork, Ruth D. (Frontiers in Medicine, 2020)
In December 2019 a cluster of severe pneumonia was observed in China, with the subsequent discovery of a new betacoronavirus (SARS-CoV-2) as the causative agent. The elicited disease COVID-19 is characterized by fever, dry cough, myalgia or fatigue and has a favourable outcome in the majority of cases. However, in some patients COVID-19 leads to severe pneumonia and sepsis with subsequent respiratory failure and gastrointestinal, haematological, neurological, cardiovascular complications. A higher risk of infection is intrinsic to active rheumatic and musculoskeletal diseases (RMD) and the use of biological disease modifying anti-rheumatic drugs (DMARDs). With an increasing number of reports on COVID-19 in RMD patients, we are beginning to appraise their risks. In this review, we summarize the published cases of COVID-19 infections in RMD patients, including patients with inflammatory arthritis, connective tissue diseases as well as anti-phospholipid syndrome and Kawasaki syndrome. Overall, patients with inflammatory arthritis do not seem to be at higher risk for infection or severe course of COVID-19. Risk for critical COVID-19 in patients with systemic inflammatory diseases such as SLE or vasculitis might be increased, but this needs further confirmation. Furthermore, we summarize the data on DMARDs used to fight SARS-CoV-2 infection and hyperinflammation.